Pengaruh Penambahan Prebiotik Inulin dari Chicory Terhadap Karakteristik Organoleptik Sinbiotik Set Yoghurt - Vegi Kurnia Navida; Minda Azhar; Iryani Iryani; Umar Kalmar Nizar (Departemen Kimia FMIPA UNP, 2021)
Increasing the functional value of yogurt can be done by combining prebiotics with probiotics, known as yoghurt set synbiotics. This study aims to determine the effect of adding inulin chicory to the organoleptic synbiotic yoghurt set. This research is an experimental research. The yoghurt synbiotics made have variations in inulin concentrations (0.1%, 0.3%, 0.5%). Preparation of yoghurt synbiotic set was carried out at an incubation time of 20 hours, temperature 37°C. The analysis of the organoleptic test results showed that in the addition of 0.3% inulin, there was a significant difference in the aroma and texture of the yogurt synbiotic set, while the color was not significant between the comparison yogurt with the addition of 0.3% inulin.